ANALISIS PROFESIONALISME, PENGETAHUAN, DAN ETIKA PROFESI AUDITOR TERHADAP PERTIMBANGAN TINGKAT MATERIALITAS PEMERIKSAAN LAPORAN KEUANGAN - Erfan Muhammad (JAFFA, 2013)
The purpose of this research is to analyze the influence of professionalism, knowledge, and professional ethics on consideration the level of materiality in examining the financial statements at registered public accountant in Surabaya. Research design is survey research using questionnaire as instrument. The respondents of leaders and partners, manager, and senior auditor at registered public accountant in Surabaya. The research population was 175 auditor at registered public accountant in Surabaya. The research sample minimum was 98 auditors. The data was analyzed using multiple regression analysis with SPSS version 12.0. The research study show that professionalism, knowledge, and professional ethics influence simultaneously on consideration the level of materiality. The effect of professionalism on consideration the level of materiality is significant, the effect of knowledge on consideration the level of materiality is significant, the effect of auditors professional ethics on consideration the level of materiality is significant.